CATEGORISATION ET CLASSIFICATION DES PLANTES ET ANIMAUX CHEZ LES TOPOKE C53, LOKELE C55 ET OLOMBO C54 - Liwila, Nicolas MOMBAYA (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2021)
The present research paper focuses on how topoké, lokelé and olombo people categorize diversity of their environment elements, for our concern, plants and animals. The main concern for this research paper is on their respective popular classifications, not on scientific taxonomy which is not the concern of our reseach field.